Internal carotid artery agenesis and contralateral middle cerebral artery infarction - Şimşek, Fatma; Aktaş, Filiz (Journal of Surgery and Medicine, 2021)
Internal carotid artery agenesis is usually an asymptomatic condition. It is detected incidentally by radiological imaging performed for other reasons. It may rarely present with clinical manifestations such as subarachnoid hemorrhage associated with aneurysm, transient ischemic attack, or stroke. Agenesis can be erroneously interpreted as occlusion in case of insufficient clinical experience. The absence of the carotid canal on the bone window in the computed tomography scan of the brain helps confirm the diagnosis. The well-developed collateral circulation in patients with internal carotid artery agenesis is an effective factor in recovering from cerebrovascular diseases with less damage. Here, a rare case of agenesis of the right internal carotid artery and contralateral middle cerebral artery infarction is presented.